PELINDUNGAN HUKUM TERHADAP MOTIF TENUN ACEH DI KABUPATEN ACEH BESAR - EVA ROSSANA DEWI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Saidin, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Dr. Jelly Leviza, SH, MHum The motif developed by weaving craftsmen in Aceh Besar District is potential to be registered as a copyright, but it is not. This problem leads to imitation or plagiarism to the motif designed by one of the craftsmen; furthermore, the craftsman does not realize the importance of registering the motif he has designed. This is a normative juridical research and is analytically descriptive. Based on the description of characteristics of weaving which is classified into the object of traditional cultural expression, it is concluded that Acehnese weaving motif can be regarded as a traditional cultural expression in accordance with article 38 paragraph (1) letter e of the Law on Copyrights. Weaving can be categorized as the combination of forms of fine arts in two or three dimensions made of textile. Weaving motifs created by the craftsmen in Aceh Besar District are included into contemporary weaving protected by Article 40 paragraph (1) letter j of the Law on Copyrights. Aceh Province Government has improved the craftsmen awareness to register their work copyrights and increase weaving product marketing outside of the area. . The protection for Acehnese weaving motif that has been made by Industry, Trading, Cooperatives, and Small to Medium Enterprises Agency of Aceh Besar Regency by carrying out socialization to particularly weaving production villages to actively supervise new creations, and developing Acehnese weaving products. Aceh Besar Regency Government makes efforts by registering new creations of Acehnese weaving motifs.Keywords: Copyrights, Traditional Knowledge, Weaving Motif.